2011
DOI: 10.1016/j.mce.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenesis and steroidogenic gene expression in postnatal fetal rat Leydig cells

Abstract: Please cite this article as: Weisser, J., Landreh, L., Söder, O., Svechnikov, K., Steroidogenesis and steroidogenic gene expression in postnatal fetal rat Leydig cells, Molecular and Cellular Endocrinology (2008), doi:10.1016/j.mce.2011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Curiously, the fetal Leydig cells had the potential to synthesize not only androstenedione but also testosterone under cAMP stimulation. Consistent with this finding, steroidogenic genes including Hsd17b3 were expressed in the rat fetal Leydig cells [Weisser et al, 2011]. Although the reasons for the contradictory conclusions obtained in the 2 studies are unknown, future studies using Leydig and Sertoli cells purified from fetal testes should provide us with a definite conclusion concerning the steroid-synthetic activity of fetal Leydig cells.…”
Section: Do Fetal Leydig Cells Synthesize Testosterone?supporting
confidence: 60%
“…Curiously, the fetal Leydig cells had the potential to synthesize not only androstenedione but also testosterone under cAMP stimulation. Consistent with this finding, steroidogenic genes including Hsd17b3 were expressed in the rat fetal Leydig cells [Weisser et al, 2011]. Although the reasons for the contradictory conclusions obtained in the 2 studies are unknown, future studies using Leydig and Sertoli cells purified from fetal testes should provide us with a definite conclusion concerning the steroid-synthetic activity of fetal Leydig cells.…”
Section: Do Fetal Leydig Cells Synthesize Testosterone?supporting
confidence: 60%
“…Moreover, CYP17A1 is one the main proteins studied in Leydig cells during toxicology experiments investigating the effects of drugs or compounds on steroidogenesis. It has been demonstrated that a change in the expression of CYP17A1 mRNA and protein may directly affect the level of testosterone [11,12]. Our results led us to believe that we have determined the pathway through which CLA affects steroidogenesis.…”
Section: Discussionmentioning
confidence: 64%
“…Second, CLA may alter steroidogenesis by up-regulating specific genes encoding enzymes and transport proteins involved in the synthesis of testosterone, such as 17α-hydroxylase/17,20-lyase (CYP17A1), which converts progesterone into androstenedione. It has been demonstrated that a change in CYP17A1 expression may directly affect the level of testosterone [11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this ex vivo approach resulted in cell death after infection with LV-COUP-TFII (data not shown). There are also inherent problems with applying similar approaches to the ex vivo culture of fetal LC, which rapidly (∼48 h) lose their steroidogenic function after isolation [24]. Therefore, to provide more definitive evidence that nuclear COUP-TFII expression in fetal LC was associated causally with reduced ITT, DBP treatment was delayed until a time-point (e19.5–e20.5;  = late treatment window) when ∼80% of LC have normally switched off nuclear expression of COUP-TFII (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that the mechanism underlying such effects involves competition between COUP-TFII and SF-1 for binding to an overlapping response element in the promoter region of genes encoding steroidogenic enzymes [18], [19], [20], [21], [23], [30], [31], [32], [33], [34], [35], [36], [37], [38], as proposed for the present studies in fetal rat LC. Unfortunately, our studies using viral transfection of ex vivo cultured rat fetal LC with COUP-TFII resulted in cell death (unpublished data), and there are also inherent problems with the culture of fetal LC, which rapidly lose their steroidogenic function [24]. Therefore, this direct approach was not an option for us.…”
Section: Discussionmentioning
confidence: 99%